Enterospora nucleophila (Microsporidia) in Gilthead Sea Bream (Sparus aurata): Pathological Effects and Cellular Immune Response in Natural Infections. Issue 4 (July 2020) - Picard-Sánchez, Amparo; Piazzon, M. Carla; Ahmed, Nahla Hossameldin; Del Pozo, Raquel; Sitjà-Bobadilla, Ariadna; Palenzuela, Oswaldo
Enterospora nucleophila is a microsporidian responsible for an emaciative disease in gilthead sea bream ( Sparus aurata ). Its intranuclear development and the lack of in vitro and in vivo models hinder its research. This study investigated the associated lesions, its detection by quantitative polymerase chain reaction, and the cellular immune response of naturally infected fish. The intensity of infection in the intestine was correlated with stunted growth and reduced body condition. At the beginning of the outbreaks, infection prevalence was highest in intestine and stomach, and in subsequent months, the prevalence decreased in the intestine and increased in hematopoietic organs and stomach. In heavy infections, the intestine had histologic lesions of enterocyte hypercellularity and proliferation of rodlet cells. Infected enterocytes had E. nucleophila spores in the cytoplasm, and a pyknotic nucleus, karyorhexis or karyolysis. Lymphocytes were present at the base of the mucosa, and eosinophilic granule cells were located between the enterocytes. In intestinal submucosa, macrophage aggregates containing spores were surrounded by lymphocytes and granulocytes, with submucosal infiltration of granulocytes. Macrophage aggregates appeared to develop into granulomata with necrotic areas containing parasite remnants. Immunohistochemistry revealed mast cells as the main type of granulocyte involved. Abundant IgM + and IgT + cells were identified by in situ hybridization in the submucosa when intracytoplasmic stages were present. This study describes the lesions of E. nucleophila in gilthead sea bream, an important aquaculture species.